"La delegacion de India durante su visita al techo de la casa CNT/FAI. D.i.a.d.: 1. (?), 2. Rodriguez Vazquez, 3. (?), 4. Menon, 5. Nehru, 6. Gandhi". Copied from CNT collection
"La delegacion de India durante su visita al techo de la casa CNT/FAI. D.i.a.d.: 1. (?), 2. Rodriguez Vazquez, 3. (?), 4. Menon, 5. Nehru, 6. Gandhi". Copied from CNT collection.